Designing carbon fiber composite interfaces using a 'graft-to' approach: Surface grafting density versus interphase penetration. (May 2019) - Randall, James D.; Eyckens, Daniel J.; Servinis, Linden; Stojcevski, Filip; O'Dell, Luke A.; Gengenbach, Thomas R.; Demir, Baris; Walsh, Tiffany R.; Henderson, Luke C.
Abstract: This paper examines the effect on interfacial shear strength (IFSS) when grafting polyethyleneoxide (PEO) polymers of various molecular weights to a carbon fiber surface. Using copper-azide-alkyne cycloaddition click chemistry, PEO polymers of 1 kDa, 2 kDa, 5 kDa, and 10 kDa were tethered to the fiber surface without causing degradation of the fiber surface. The resulting IFSS increases were maximised (130% and 160%) for the 1 kDa and 10 kDa surface modified fibers, respectively. These data suggest that increases in IFSS are the result of an interplay between the density of surface modification versus the penetration of the grafted polymer into the matrix interphase. The trade-off between interphase penetration and surface grafting density is highlighted for the 2 and 5 kDa PEO chains on the fiber surface which display smaller IFSS increases (85% and 117%, respectively). Measuring the mobility of the PEO polymers by 1 H NMR found an order of magnitude decrease in diffusion coefficient for each successive increase in molecular weight, supporting the hypothesis that grafting density decreases with molecular weight. Molecular dynamics simulations of the carbon fiber-matrix interface further supports these observations. These results will inform the design of complementary interfaces for various materials in a range of supporting media. Graphical abstract: Image 1